A Comprehensive Survey on Transmitting Antenna Systems With Synthesized Beams for Microwave Wireless Power Transmission - Lu, Ping; Wagih, Mahmoud; Goussetis, George; Shinohara, Naoki; Song, Chaoyun (IEEE journal of microwaves, 2023)
In recent years, microwave wireless power transmission (MWPT) has emerged as a promising technology for supplying energy by receiving radiative power without wires and converting it into DC power. A high transmission efficiency is crucial for improving the performance of MWPT systems. To address the challenge of propagation loss, beam synthesis using transmitting antennas has gained significant attention, resulting in several synthesis methods becoming available, including whisper beams, flat-top beams, non-diffractive beams, supergain/superdirective beams, focused beams and adaptive beamforming technique such as time reversal methods. This comprehensive review covers these advanced beam synthesis techniques for MWPT transmitters and provides a detailed comparison of different synthesized beams. The article includes an in-depth discussion on current designs and existing technological challenges, as well as suggestions for future research directions. Although beam synthesis can substantially improve the transmission efficiency, the overall power transfer efficiency of the entire MWPT system still requires improvement as the performance, including impedance matching, is currently only considered at a component level and not at a system level. Furthermore, when using advanced beam synthesis techniques, the engineering and implementation challenges of high power (≥kW) and long-distance (≥km) MWPT become significant issues due to the high cost and large size involved. The review concludes that existing technologies for synthesized beams still require significant long-term efforts to meet the realistic engineering requirements for achieving highly efficient MWPT systems. The joint utilization of beam synthesis techniques and comprehensive system matching/optimization is identified as a research direction with the potential to realize highly efficient MWPT systems, offering foreseeable impacts in both terrestrial and space-based MWPT applications. This review serves as a solid foundation for the design of transmitter antennas in long-distance, high-power MWPT systems, and furthermore provides novel insights for future designs of highly efficient MWPT systems.